Large pulmonary arteriovenous malformation lost to follow-up with 10 years of asymptomatic interval growth: A case report - Nicholas W. Kemper, MD; Alexander C. Myers, MS; Hanna K. Thompson, MD; Nana Ohene Baah, MD; Sohail Contractor, MD, FSIR (Radiology Case Reports, 2024)
Pulmonary arteriovenous malformations, previously considered a rare condition, have been increasingly identified in asymptomatic patients over the past 2 decades. Usually congenital and associated with hereditary hemorrhagic telangiectasia, these fistulae result in right-to-left shunting of blood by abnormal communication of pulmonary arteries and veins lacking capillary beds. Clinical findings of right-to-left shunting in the presence of feeding and draining vessels identified on imaging confirm the diagnosis, for which the first-line therapy is embolization. This report highlights the presentation and management of a large asymptomatic PAVM detected incidentally in a patient who was lost to follow-up for 10 years and represented with acute hypoxic respiratory failure secondary to a viral infection with an interval increase of PAVM size.